Remote robotics, or the digital re-embodiment of labour - James Steinhoff; Julian Posada; Alessandro Delfanti (Work Organisation, Labour and Globalisation)
The remote operation of robots in logistics is becoming increasingly prevalent, with robots being deployed across a variety of sectors and operated by workers from a distance. This allows manual labour to be conducted remotely. Despite eliminating the need for physical proximity between the robot and the operator, remote robotics still necessitates human interaction to control the machinery, a process we call re-embodiment. This working arrangement introduces constraints on the communities and territories of remote workers. Rather than deviating from traditional labour practices, remote robotics extends the reach of capital and perpetuates existing patterns of exploitation.